INVESTMENT ATTRACTIVENESS OF SERVICE ENTERPRISES: METHODOLOGICAL BASES - Islom Ergashev (European Journal of Interdisciplinary Research and Development, 2023)
This scientific article considers investment activity, which includes a set of practical actions related to investing and making a profit. She explains the two main stages of this activity: the introduction of funds and the result of investment. The article also emphasizes the connection between investment activity and the investment attractiveness of enterprises. Describes various approaches to the concept of investment attractiveness and offers a definition, as well as discusses the role of investment in the development of the economy.